Functions of propolis as a natural feed additive in poultry. Issue 1 (1st March 2016) - Mahmoud, U.T.; Cheng, H.W.; Applegate, T.J.
Abstract : Propolis is a resinous hive product collected by honeybees from various sources of plants. Numerous scientific investigations have been focused on the biological activities of propolis and its functions as a health supplement in humans. It could have similar function in other animals, such as in poultry. This review is focused on the recent findings concerning the effects of propolis, as an antioxidant, on performance, carcass characteristics, behaviour, immunity, and physiological homeostasis in domesticated poultry species (broiler chickens, laying hens, quail, and duck); and the needs in future poultry research.